THE ECONOMIC INDEPENDENCE OF WOMEN IS THE CONTRIBUTION OF THE FAMILY TO LIVING WELL (Scientific journal of the Fergana State University, 2025)
The article tried to convey about the role of women in public social life, about the positive impact of her cocktail on the environment in the family. This issue, the problems of ensuring employment of women, the usefulness to society, the problems of fulfilling their role in the family, the equality of the duties of mother and father in the upbringing of children. To this end, a number of decisions have been made by the Government of the Republic, speaking about the work carried out in ensuring their implementation.